PENERAPAN ALGORITMA C4.5 UNTUK DIAGNOSA STATUS GIZI PADA ANAK BALITA BERBASIS WEBSITE - Rusda Wajhillah; Erika Mutiara (Swabumi, 2016)
Nutritional status of infants is an important factor that must be considered sinceinfancy is a period of development with a range of nutrients. Nutritional statuscan be divided into three indicators of good nutrition, malnutrition andmalnutrition. C4.5 classification algorithm is an algorithm that can produceeasily interpreted decision tree, have an acceptable level of accuracy, efficient inhandling discrete and numeric-type attributes (Kamagi dan Seng, 2014).Therefore, in this study will be conducted data analysis nutritional status inchildren under five using the classification of the data mining algorithm C4.5using four variabels: gender, age (months), weight (kg) and height (cm). Based onthese descriptions, we need a system that can represent an expert who has theknowledge base and experience of diarrheal disease, which is an expert system.From 108 infants amount of data that consists of 92 data subject to a goodnutrition and 16 data were experiencing malnutrition among children under fiveare obtained from Posyandu Nyangkowek, then obtained 17 rules resulting fromC4.5 decision tree algorithm with good nutrition as class numbers 12 and thenumber of undernourished class so much as 5 rules, so that it can be concludedthat the research that is implemented into a web application can help users,particularly parents in diagnosing the nutritional status of children under five.